Spatial behavior in rehabilitated orangutans in Sumatra: Where do they go? - Dominik Fechter; Simone Ciuti; Doris Kelle; Peter Pratje; Carsten F Dormann; Ilse Storch (PLoS ONE, 2019)
Wildlife restoration is one of the key components of conservation strategies, and this includes the rehabilitation and release of animals confiscated from wildlife traffickers. When primates are re-introduced, most individuals need a pre-release training to acquire the skills needed to survive in the wild. Pre-release training may either negatively or positively affect primate post-release behavior and survival. Post-release behavior, however, has rarely been monitored even though it is the only means to assess the survival of released individuals. Here, we present a thorough analysis of data from a 3-year radio tracking study on 32 orangutans (Pongo abelii) released in Sumatra after their rehabilitation. We investigated whether and how the age at release, the duration of the pre-release rehabilitation and training, and the release location affected the post-release individual spatial behavior. Orangutans released at older age exhibited post-release habitat selection patterns that were more comparable to that shown by wild conspecifics, i.e., they chose areas closer to rivers and at lower elevations (150-250 meters a.s.l.) where previous research had documented greater food availability. In contrast, individuals released at younger age showed a stronger spatial dependency on the rehabilitation station and exhibited disrupted habitat selection patterns; although after several months after the release all individuals tended to decrease their spatial reliance on the rehabilitation facility. This study indicates that the rehabilitation of individuals for a longer period and their release further from the rehabilitation station have facilitated the subsequent development of more natural spatial behavior, i.e. driven by food availability rather than by the dependence on care-giving human facility. Our study provides indications on how to improve the rehabilitation and release of confiscated orangutans, highlighting the importance of the age at release, the length of the rehabilitation program, and the location of the release site.